Does the knowledge of emergency contraception affect its use among high school adolescents? - Christiane Borges do Nascimento Chofakian; Ana Luiza Vilela Borges; Ana Paula Sayuri Sato; Gizelton Pereira Alencar; Osmara Alves dos Santos; Elizabeth Fujimori (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2016)
Abstract This study aimed to test how knowledge on emergency contraception (according to age at sexual initiation, type of school, and knowing someone that has already used emergency contraception) influences the method's use. This was a cross-sectional study in a probabilistic sample of students 15-19 years of age enrolled in public and private middle schools in a medium-sized city in Southeast Brazil (n = 307). Data were collected in 2011 using a self-administered questionnaire. A structural equations model was used for the data analysis. Considering age at sexual initiation and type of school, knowledge of emergency contraception was not associated with its use, but knowing someone that had used the method showed a significant mean effect on use of emergency contraception. Peer group conversations on emergency contraception appear to have greater influence on use of the method than knowledge itself, economic status, or sexual experience.